Объяснение:
7x+10=5x+2
7х-5х=2-10
2х=-8
х=-8:2
х=-4
4(3x-2) +5=9
4(3х-2)=9-5
4(3х-2)=4
3х-2=4:4
3х-2=1
3х=1+2
3х=3
х=3:3
х=1
2x-5=7(3x+4) +5
2х-5=21х+28+5
2х-21х=28+5+5
-19х=38
х=38:(-19)
х=-2
7x-5x=2-10
2x=-8
x=-8/2
x=-4
12x-8+5=9
12x=9+8-5
12x=12
x=12/12
x=1
2x-5=21x+28+5
2x-21x=28+5+5
-19x=38
X=38/-19
x=-2
Объяснение:
7x+10=5x+2
7х-5х=2-10
2х=-8
х=-8:2
х=-4
4(3x-2) +5=9
4(3х-2)=9-5
4(3х-2)=4
3х-2=4:4
3х-2=1
3х=1+2
3х=3
х=3:3
х=1
2x-5=7(3x+4) +5
2х-5=21х+28+5
2х-21х=28+5+5
-19х=38
х=38:(-19)
х=-2
7x-5x=2-10
2x=-8
x=-8/2
x=-4
12x-8+5=9
12x=9+8-5
12x=12
x=12/12
x=1
2x-5=21x+28+5
2x-21x=28+5+5
-19x=38
X=38/-19
x=-2